COMPUTATIONAL PREDICTION OF B-CELL AND T-CELL SPECIFIC PEPTIDE VACCINE AGAINST ELIZABETHKINGIA MENINGOSEPTICA - Tania Michael and Sathish Sankar* (Chelonian Research Foundation, 2023)
Elizabethkingia meningoseptica is an opportunistic pathogen associated with nosocomial infections, particularly in immunocompromised individuals. Despite its clinical significance, there is a lack of targeted vaccines against this bacterium. The development of effective vaccines requires a comprehensive understanding of the specific immune responses, particularly those mediated by B-cells and T-cells.The identified B-cell and T-cell epitopes demonstrated strong antigenicity and immunogenicity. The multi-epitope subunit vaccine induced a robust humoral and cellular immune response.This study presents a comprehensive strategy for the identification of B-cell and T-cell-specific vaccine candidates for E. meningoseptica. Using a combination of bioinformatics and immunoinformatics approaches, potential antigens were identified for their ability to elicit robust B-cell and T-cell responses. Epitope prediction algorithms were employed to identify B-cell epitopes with high antigenicity, surface exposure, and conservation. T-cell epitopes were predicted based on major histocompatibility complex (MHC) binding affinity, ensuring immunogenicity.The selected antigens and epitopes hold promise for the development of a targeted vaccine against this pathogen. Future studies will focus on the in vivo efficacy of the vaccine candidates, potentially paving the way for clinical trials and the development of a much-needed preventive tool against E. meningoseptica infections. This study aimed to identify B-cell and T-cell specific vaccine candidates for E. meningoseptica, focusing on antigens that elicit robust immune responses and confer protection against infection. Keywords-Universal health, diseases,well being,international health policy,Elizabethkingia meningoseptica, peptide vaccine.